Youth and the Drought: Exploring the Pro-Environmental Behavior of the Resan Communities in Revitalizing Local Springs in Gunungkidul Regency - Dwiananta, Yoga Epri; Rissaldy, Jovian Dito; Asih, Siti Puji; Pradiana, Yolla; Ulhaq, Muhammad Fathi Dhiya; Permadi, Dwiko Budi (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Pro-environmental behavior is increasingly demonstrated by the younger generation across the globe. In Gunungkidul, a rural region of Indonesia, the young generation initiated the resan community that emerged in response to the Cempaka hurricane of 2017, focusing on revitalizing local springs as reservoirs to mitigate prolonged dry seasons caused by climate change. This study explores the formation, worldviews, and perceptions surrounding the resan community’s activities through in-depth interviews, participant observation, and social media analysis. Spanning 42 of Gunungkidul’s 144 villages, this youth-driven movement is rooted in Javanese cultural values, emphasizing water conservation and community resilience through local wisdom, tacit knowledge, and grassroots participation. Diverse perceptions about resan reflect an ongoing dialogue that requires further attention from stakeholders and policymakers. The Resan Gunungkidul Community provides a platform for individuals who care about the environment and wish to contribute to conservation efforts. Community participation, especially the young generation, is a cornerstone of this initiative, promoting water conservation rooted in collective action. The study highlights the importance of integrating localized efforts like tree planting with broader multidisciplinary approaches, aligning with global practices of ecological preservation and sustainable development.